The Impact of the KPK Law Revision on Prosecutorial Authority - Moch Ridwan Affandi; Siti Marwiyah; Vieta Imelda Cornelis (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
Corruption is an extraordinary crime that has far-reaching impacts on state finances, the legal system, and public trust. In combating corruption, the Corruption Eradication Commission (Komisi Pemberantasan Korupsi/KPK) and the Public Prosecutor’s Office (Kejaksaan) play strategic roles, particularly in the prosecution of corruption cases. However, the amendment of Law Number 30 of 2002 into Law Number 19 of 2019 on the Corruption Eradication Commission has brought significant changes to the institutional position and authority of the KPK, affecting its relationship with the Prosecutor’s Office. This study aims to analyze the policies of the KPK and the Prosecutor’s Office in regulating prosecutorial authority and to examine the implications of the amendment to the KPK Law for the effectiveness of corruption law enforcement in Indonesia. This research employs an empirical legal research method using statutory, conceptual, and empirical approaches through interviews, observation, and literature review. The findings indicate that the amendment to the KPK Law has strengthened coordination and oversight mechanisms, but at the same time has posed challenges to the independence and speed of prosecution. Therefore, the effectiveness of corruption eradication after the amendment largely depends on strengthening institutional synergy, clarifying the division of authority, and ensuring consistency in prosecutorial policies between the KPK and the Prosecutor’s Office.